Sediment grain-size, age-depth model, and hydrodynamic skin-friction parameters from IODP Expedition 354 Site U1451, Bay of Bengal, since the Late Miocene - Manoj, M C; Kawsar, Masud; Weber, Michael E (PANGAEA, 2025)
This dataset contains age–depth relationships, sortable silt grain-size distributions, and derived hydrodynamic parameters from sediments recovered during IODP Expedition 354 at Site U1451 (Bay of Bengal). Grain-size analyses were conducted using a Beckman Coulter laser diffraction particle-size analyzer. Sedimentary texture fractions (<10 µm cohesive, 10–63 µm non-cohesive silt, and >63 µm sand) were quantified, and hydrodynamic parameters (skin friction shear stress, critical shear stress) were calculated to discriminate hemipelagic from turbiditic deposition. The dataset supports interpretations presented in Kawsar et al. (2023, Geo-Marine Letters).
Keywords: Bengal Fan; Deposition dynamics; Sediment threshold; Shields diagram; sortable silt